Cinematography Strategies in Promoting Local Culture: A Study of the Documentary ‘It’s More than Candlenut Indudur. - Sri Dwi Astuti Al Noor; Stefvany; Yosa Fiandra; Arief Budiman; Mohammad Firdaus Azman (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2025)
Nagari Indudur, located in IX Koto Sungai Lasi District, Solok Regency, West Sumatra, is a major producer of candlenut oil. With an annual contribution of Rp. 147,350,000, candlenut oil plays a crucial role in the local economy. However, limited accessibility and promotion remain major challenges for farmers.To support the introduction of candlenut oil products, the Indonesian Conservation Community (KKI) WARSI produced a short documentary titled "It’s More Than Candlenut Indudur." This film aims to promote Indudur’s traditional candlenut oil to national and international audiences. This research employs a qualitative descriptive method to analyse the cinematographic techniques used in the film, including aerial cinematography, the application of the rule of thirds composition, as well as drone shots and other cinematic techniques. The study findings indicate that visual techniques such as eagle-eye angle, high angle, composition in framing, and camera movements like dolly-in-out and following shots effectively showcase the topographical beauty and the activities of candlenut oil farmers in an aesthetic and informative manner. With a duration of 6 minutes and 27 seconds, this film delivers a strong visual narrative, supported by Minang-language audio and subtitles, to highlight Indudur’s potential as a producer of high-quality candlenut oil. The results of this study provide insights into the importance of a cinematic approach, referring to how visuals are used to convey narratives emotionally and immersivity in documentary films aimed at promoting local products while also supporting the economic sustainability of rural communities in remote areas.